Variations of ankle-foot orthosis-constrained movements increase ankle range of movement while maintaining power output of recumbent cycling - Hamdan, Puteri N.F.; Hamzaid, Nur Azah; Usman, Juliana; Islam, Md Anamul; Kean, Victor Shern Phng; Wahab, Ahmad Khairi Abdul; Hasnan, Nazirah; Davis, Glen Macartney (De Gruyter, 2018)
Previous research investigated recumbent cycle power output (PO) from the perspective of knee and hip joint biomechanics. However, ankle-foot biomechanics and, in particular, the effect of ankle-foot orthosis (AFO)-constrained movements on cycle PO has not been widely explored. Therefore, the purpose of this study was to determine whether AFOs of a fixed position (FP) and in dorsi-plantarflexion (DPF)-, dorsiflexion (DF)- and plantarflexion (PF)-constrained movements might influence PO during voluntary recumbent cycling exercises. Twenty-five healthy individuals participated in this study. All underwent 1-min cycling at a fixed cadence for each of the AFOs. The peak and average PO of each condition were analyzed. The peak and average PO were 27.2±12.0 W (range 6-60) and 17.2±9.0 W (range 2-36), respectively, during voluntary cycling. There were no significant differences in the peak PO generated by the AFOs (p=0.083). There were also no significant differences in the average PO generated using different AFOs (p=0.063). There were no significant differences in the changes of the hip and knee joint angles with different AFOs (p=0.974 and p=1.00, respectively). However, there was a significant difference in the changes of the ankle joint angle (p<0.00). The present study observed that AFO-constrained movements did not have an influence in altering PO during voluntary recumbent cycling in healthy individuals. This finding might serve as a reference for future rehabilitative cycling protocols.